2019
DOI: 10.3390/coatings9110705
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Roles of Zinc in a Porous Titanium Dioxide Layer Formed by Micro-Arc Oxidation

Abstract: This study investigated the time transient effect of zinc (Zn) in the porous titanium dioxide formed by micro-arc oxidation (MAO) treatment routinely performed for Zn-containing electrolytes. The aim of our analysis was to understand the changes in both the chemical and biological properties of Zn in physiological saline. The morphology of the Zn-incorporated MAO surface did not change, and a small amount of Zn ions were released at early stages of incubation in saline. We observed a decrease in Zn concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 82 publications
(94 reference statements)
2
26
1
Order By: Relevance
“…MAO easily and selectively incorporates the required elements into the titanium surface owing to the compositional control in the electrolyte. Table 2 summarizes the published articles related to the one-step MAO-based incorporation of antibacterial elements onto the Ti surface [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. It should be noted that some researchers have combined MAO and other surface modification processes [ 103 , 104 , 105 , 106 ].…”
Section: Micro-arc Oxidation (Mao)mentioning
confidence: 99%
See 3 more Smart Citations
“…MAO easily and selectively incorporates the required elements into the titanium surface owing to the compositional control in the electrolyte. Table 2 summarizes the published articles related to the one-step MAO-based incorporation of antibacterial elements onto the Ti surface [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. It should be noted that some researchers have combined MAO and other surface modification processes [ 103 , 104 , 105 , 106 ].…”
Section: Micro-arc Oxidation (Mao)mentioning
confidence: 99%
“…Huang et al reported that the Cu-incorporated surface contributed to the improvement of both the macrophage-mediated bone formation and bactericidal capacity [ 86 ]. In addition to the incorporation of other elements, large amount sof Zn on the Ti surface exhibited cytotoxicity against osteoblasts, and a suitable amount of Zn promoted its response [ 71 , 85 , 95 , 97 ]. Hence, the quantitative control of the incorporation of Ag, Cu, and Zn plays a key role in the dual-functionalization of the Ti surface by MAO.…”
Section: Dual-functionalization By Maomentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray photoelectron spectroscopy (XPS; JPS-9010MC, JEOL, Tokyo, Japan) was used in this investigation. The detail of the measurement condition was 10 kV of acceleration voltage, 10 mA of current, MgKα (energy: 1253.6 eV) of X-ray source, and was described in our previous study [40]. The calibration of the binding energy was performed based on C 1s photoelectron energy region peak derived from contaminating carbon (285.0 eV).…”
Section: Surface Characterizationmentioning
confidence: 99%